Opera after Stalin: Rodion Shchedrin and the search for the voice of a new era - Schneider, H (2021)
Until recently, Russian opera after Stalin has been an almost entirely neglected topic. In this thesis, I analyse the development of operatic style and culture in Russia between 1953- 2020 by examining four operas by the most prominent late Soviet and post-Soviet composer, Rodion Shchedrin, and by bringing these operas into conversation with those of his peers during each phase of his career. Mining previously untapped archival sources, I set opera in dialogue with aspects of Soviet cultural history, engaging with the central themes that have occupied scholars of the late Soviet and post-Soviet periods: Socialist Realism, modernism, consumer culture, relations with the West, political ideology, Soviet morality, religious revival, and negotiations with power and censorship. In Chapter 1, I address the re-formation of operatic standards during the Thaw, using the bizarre production history of Shchedrin’s first opera, Not Love Alone (1961) as a case study. Chapter 2 explores the operatic culture of the 1970s, identifying four major camps of composers: the ‘officials’, the ‘rebels’, the revival of 1920s modernism, and the fourth way – Shchedrin, and his opera Dead Souls (1976). Chapter 3 probes the fault lines of Perestroika exploiting the lens of Shchedrin’s third opera, Lolita (1989-1994), and examines the musical and professional fate of composers navigating this transition. In Chapter 4, I analyse Russian opera in the twenty-first century. First, I expose the contemporary culture of censorship that has developed in the past two decades, and its effect on opera; next, I chronicle the formation of a new style in Russian opera that is both national and divergent from trends in Western opera: ‘Russianist Realism’. I demonstrate how Shchedrin’s adaptability, which helped him thrive in the Soviet era, has enabled him to meet the demands of a new political moment, and rise to a position of prominence among living Russian composers. Ultimately, I hope this thesis will contribute to the growing literature addressing the need for closer scrutiny of Soviet life and culture after Stalin, and especially, that it will spark new interest in late Soviet and post-Soviet opera.